Animasi Motion Graphic Sebagai Media Pembelajaran Sistem Tata Surya Untuk Siswa Kelas 6 Sekolah Dasar - Ika Asti Astuti; Safira Nada Athaya (Sekawan Institut, 2023)
Along with the rapid development of information technology today, multimedia has an important role in the field of education. Studying the solar system is very important, especially for elementary school children because it is very closely related to other natural sciences. In learning activities, the delivery of solar system material in schools is only conventional and theoretical which is equipped with several static examples, so that most students have difficulty and do not even like the lesson. Therefore, it is necessary to have an application that explains the characteristics of the Solar System with animations and visualizations that can support elementary school students in understanding the solar system easily and not boringly. One alternative media that can attract children's attention is video motion graphics. The method in this study applies the 4D model which includes four stages: (1) define, (2) design, (3) develop and (4) disseminate. The evaluation used is alpha testing and usability questionnaires for 6th grade elementary school students. The results of this research are 2D animated videos about the solar system which are made according to the needs and help learning activities of the solar system.